2000
DOI: 10.1034/j.1600-0854.2000.010507.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathway for Transport and Metabolism of a Fluorescent Phosphatidic Acid Analog in Yeast

Abstract: The various membranes of a cell have distinctive lipid compositions and membrane structures that are necessary for the specific functions of each membrane and compartmentalization of biochemical pathways. Movement of phospholipids between and within membranes is essential for the development and maintenance of this specialized membrane organization. A vast amount of data have been generated toward describing processes of intracellular lipid transport, revealing that lipids of the various classes are transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…At this temperature, Ͼ80% of the internalized lipid could be recovered in the intact form (unpublished data). NBD-PA uptake in yeast has previously been reported to occur via a nonendocytic pathway and independent of ATP (Trotter, 2000). However, we observed that ATP-depletion of wild-type cells caused a major reduction in the uptake of both NBD-PA (82%) and NBD-PG (85%; Figure 5A and unpublished data).…”
Section: The Lipid Translocation Defect In ⌬Dnf1⌬dnf2 Cells Is Specificcontrasting
confidence: 43%
“…At this temperature, Ͼ80% of the internalized lipid could be recovered in the intact form (unpublished data). NBD-PA uptake in yeast has previously been reported to occur via a nonendocytic pathway and independent of ATP (Trotter, 2000). However, we observed that ATP-depletion of wild-type cells caused a major reduction in the uptake of both NBD-PA (82%) and NBD-PG (85%; Figure 5A and unpublished data).…”
Section: The Lipid Translocation Defect In ⌬Dnf1⌬dnf2 Cells Is Specificcontrasting
confidence: 43%
“…We accomplished these goals in two ways; the first was through the use of S. cerevisiae, an organism that lacks all nuclear hormone receptors and contains only a single G protein-linked receptor for mating factor. Yeast will accumulate intact anionic phospholipids from their media (30) and can be stably transfected with a PPAR␥ reporting system (18). We found (Fig.…”
Section: Lpa Binds and Activates Ppar␥mentioning
confidence: 81%
“…[Methyl‐ 14 C]‐choline was from ICN Biomedicals (Irvine, CA) and L ‐3‐phosphatidyl [ N‐ methyl‐ 3 H]‐choline,1,2‐dipalmitoyl from Amersham Pharmacia (Piscataway, NJ). NBD‐DAG was produced from NBD‐PC by treatment with phospholipase C from Bacillus cereus as described (Trotter, 2000). All other lipids and chemicals were from Sigma Aldrich (St Louis, MO), as listed in Supplementary data.…”
Section: Methodsmentioning
confidence: 99%